Business Intelligence Market Analysis for Small and Medium Enterprises - Svoboda, Jakub (2013)
The main objective of this is to select the most appropriate business intelligence solution for particular small company in accordance with its current conditions and stated criteria and with using the results obtained in the market analysis. The results of solution selection showed that the most appropriate solution for the examined company is MS SQL Server 2008 R2. To achieve this result, this thesis is divided into four parts. The first part focuses on theoretical aspects of business intelligence in order to familiarize the reader with topic related terms, history, recent trends and architecture. The second part examines the attitude of small and midsize businesses towards business intelligence. The third part of this thesis analyzes business intelligence market according to stated criteria and aspects for examination. The outcomes of this analysis were used for the following last part of this thesis which is the business intelligence project for particular small company. The project objective was to select the most appropriate solution for that company and the selection was devised on the basis of company analysis, interviews with the staff and solutions comparison in stated criteria. The major contributions are especially the third and fourth part of this thesis. On the basis of the market analysis and project was selected the most appropriate solution for particular small company.